Differentiation of Motor Neuron-Like Cells from Tonsil-Derived Mesenchymal Stem Cells and Their Possible Application to Neuromuscular Junction Formation - Park, Saeyoung (Int J Mol Sci, 2019)
Human tonsil-derived mesenchymal stem cells (T-MSCs) are newly identified MSCs and present typical features of MSCs, including having the differentiation capacity into the three germ layers and excellent proliferation capacity. They are easily sourced and are useful for stem cell therapy in various disease states. We previously reported that T-MSCs could be differentiated into skeletal myocytes and Schwann-like cells; therefore, they are a promising candidate for cell therapies for neuromuscular disease. Motor neurons (MNs), which regulate spontaneous behavior, are affected by a wide range of MN diseases (MNDs) for which there are no effective remedies. We investigated the differentiation potential of MN-like cells derived from T-MSCs (T-MSC-MNCs) for application to therapy of MNDs. After the process of MN differentiation, the expression of MN-related markers, including Islet 1, HB9/HLXB9 (HB9), and choline acetyltransferase (ChAT), was increased when compared with undifferentiated T-MSCs. The secretion of acetylcholine to the conditioned medium was significantly increased after MN differentiation. We cocultured T-MSC-MNCs and human skeletal muscle cells, and confirmed the presence of the acetylcholine receptor clusters, which demonstrated the formation of neuromuscular junctions. The potential functional improvements afforded by these T-MSC-MNCs could be useful in the treatment of MNDs caused by genetic mutation, viral infection, or environmental problems.